Empirical Analysis of Agricultural Commodity Prices, Crude Oil Prices and US Dollar Exchange Rates Using Panel Data Econometric Methods - Rezitis, Anthony (International Journal of Energy Economics and Policy, 2015)
This study examines the long-run relationship between crude oil prices, US dollar exchange rates and the prices of thirty selected international agricultural prices and five international fertilizer prices using panel econometric methods with and without unobserved heterogeneous effects on data sets of the period from June 1983 to June 2013. The empirical results indicate that in the long run the impact of crude oil price changes on agricultural prices is positive and statistically significant, while the impact of US dollar exchange rate changes is negative and statistically significant. Furthermore, the effect of US dollar exchange rate changes on commodity prices is stronger than that of crude oil price changes. The present study estimates the speed of adjustment of agricultural commodity prices towards the long-run equilibrium and the empirical results indicate that agricultural commodity prices adjust slowly towards the long-run equilibrium. Furthermore, the results of this study indicate that when unobserved heterogeneous effects with common factors are considered, the effects of oil prices and US dollar exchange rates on agricultural commodity prices are much weaker than in the case in which such effects are not considered. Finally, the persistent movements of agricultural prices are mostly attributed to the first common factor, which is closely related to the US dollar exchange rates, while the short-lived deviations of agricultural commodity prices away from their long-run equilibrium level might be due to the remaining four stationary common factors, which are capturing factors affecting the world supply and demand conditions of the international agricultural prices. Keywords: Agricultural commodity prices; Oil prices; Exchange rates; Panel cointegration; Panel error correction; Unobserved heterogeneity; Common factors JEL Classifications: C01; C32, O13